2020
DOI: 10.1161/circinterventions.119.008620
|View full text |Cite
|
Sign up to set email alerts
|

Acute Coronary Syndrome Following Transcatheter Aortic Valve Replacement

Abstract: Background: Scarce data exist on coronary events following transcatheter aortic valve replacement (TAVR), and no study has determined the factors associated with poorer outcomes in this setting. This study sought to determine the clinical characteristics, outcomes, and prognostic factors of acute coronary syndrome (ACS) events following TAVR. Methods: Multicenter cohort study including a total of 270 patients presenting an ACS after a median time of 12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 34 publications
6
29
0
Order By: Relevance
“…This study also found that only 53.3% of patients who required coronary access post‐AVR returned to the same hospital where they received their initial AVR. This finding emphasizes the need for all catheterization facilities to be facile in managing coronary engagement and PCI through especially a transcatheter aortic valve, particularly since many patients may require treatment for an acute coronary syndrome after having an TAVR 18,19,31 . Although this study demonstrated that the need for coronary engagement was significantly higher for TAVR patients who had PCI 6 months prior to their AVR and for TAVR patients with a history of CAD, this study does not address whether coronary revascularization prior to TAVR improves clinical outcomes.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…This study also found that only 53.3% of patients who required coronary access post‐AVR returned to the same hospital where they received their initial AVR. This finding emphasizes the need for all catheterization facilities to be facile in managing coronary engagement and PCI through especially a transcatheter aortic valve, particularly since many patients may require treatment for an acute coronary syndrome after having an TAVR 18,19,31 . Although this study demonstrated that the need for coronary engagement was significantly higher for TAVR patients who had PCI 6 months prior to their AVR and for TAVR patients with a history of CAD, this study does not address whether coronary revascularization prior to TAVR improves clinical outcomes.…”
Section: Discussionmentioning
confidence: 82%
“…However, given the progressive nature of CAD, these lower risk and younger patients may more likely develop symptomatic CAD post AVR given their longer survival horizon, increasing the need for future coronary reaccess and transcatheter revascularization. The consensus across studies that have evaluated PCI and angiograms after an AVR is that in both SAVR and TAVR coronary access and PCI is possible and relatively safe, but can be challenging depending on patient‐prosthesis geometric relationships 7,9,17–22,25–31 . Despite the importance of CAD post‐AVR, scant data exists regarding the need for coronary access post AVR, and understanding of post‐TAVR and post‐SAVR PCI frequency would help inform procedural planning and potentially valve selection.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, recent studies reported that half of NSTEMI following TAVR was type 2 NSTEMI, 8,9 suggesting that type 2 NSTEMI is common and is treated without an invasive coronary strategy in this population. Although we could not distinguish between type 1 and type 2 NSTEMI in the present study, a new ICD-10 code for type 2 MI (I21.A1) has started to be used since October 2017.…”
Section: Discussionmentioning
confidence: 97%
“…Access to coronary arteries following TAVI has been reported to be challenging[ 28 - 30 ]. This was highlighted with self-expanding compared to balloon-expanding valves[ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…This should not be surprising since other mechanisms of MI were proposed such as coronary embolism secondary to subclinical leaflet thrombosis, late migration of the bioprosthetic valve, impaired coronary flow dynamic, and coronary hypo-perfusion related the valve bio-prosthesis[ 32 ]. Moreover, Faroux et al [ 30 ] showed that most coronary lesions were newly developed lesions that were not flow limiting prior to their valve procedure in patients presenting with acute coronary syndrome following TAVI[ 30 ]. This was reflected in our data whereby there was no difference in events rates according to the presence of flow limiting lesions before TAVI.…”
Section: Discussionmentioning
confidence: 99%